2021
DOI: 10.3390/ijgi10080498
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Machine Learning Analysis of Social Media Data and Refugee Movement Statistics

Abstract: In 2015, within the timespan of only a few months, more than a million people made their way from Turkey to Central Europe in the wake of the Syrian civil war. At the time, public authorities and relief organisations struggled with the admission, transfer, care, and accommodation of refugees due to the information gap about ongoing refugee movements. Therefore, we propose an approach utilising machine learning methods and publicly available data to provide more information about refugee movements. The approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…We retrieved Tweets using both the REST and the streaming API of Twitter, via which georeferenced data can be accessed. In our data collection approach, we followed [18,43].…”
Section: Data Collection and Labellingmentioning
confidence: 99%
See 1 more Smart Citation
“…We retrieved Tweets using both the REST and the streaming API of Twitter, via which georeferenced data can be accessed. In our data collection approach, we followed [18,43].…”
Section: Data Collection and Labellingmentioning
confidence: 99%
“…One possibility is to extract explicitly georeferenced Tweets, most of which become geocodable via a "place" tag set by the user for the respective Tweet. Numerous studies have already shown that significant statements on geo-social phenomena can be derived from this selection [17][18][19][20][21]. A major difficulty, however, is reducing the large, rather unstructured amount of data for each use case, i.e., to consider only relevant Tweets.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in which immigration movements from the Near East towards Central Europe between 2015 and 2016 were examined, the hot spots were mostly detected either on the routes of the refugees and immigrants towards Central Europe or the Western border of Turkey where most refugees and immigrants started their journey (Havas et al, 2021). Analyses revealed that refugees and immigrants with moderate and high socioeconomic status used a wide area, they travelled long distances, and those with low socioeconomic status seemed to be trapped in small neighbourhoods (Kilic et al, 2019).…”
Section: Immigration Journeymentioning
confidence: 99%
“…To extract meaningful information from the myriad of posts at hand, computational methods such as topic modeling [3,4] and sentiment analysis [1,2,5] have been researched and adapted specifically for short-form textual social media data. In practice, this allows for the analysis and monitoring of a variety of real-world phenomena such as earthquakes [6,7], floodings [8,9], refugee movements [10] or disease outbreaks [11][12][13] through social media data.…”
Section: Introductionmentioning
confidence: 99%